Human motor behaviour. An outline of a system-theoretical approach. - Wacław Petryński (Journal of Kinesiology and Exercise Sciences)
The author presents a system-theoretical approach (STA) to the issue of the construction and control of motor operations in humans. It is based on the theory of Nikolai Bernstein, who developed a neurophysiological model called the ‘brain skyscraper’, of a systemic nature. Taking it as a model, a functional equivalent of a skyscraper, a modalities’ ladder, was developed. The common denominator of both these mental structures is the system-theoretical basis for the construction and control of motor operations in humans. The science of human motor behaviour – anthropokinetics – eludes mathematical description and explanation, which works well in physics. STA, however, seems to be a promising method of revealing specific aspects of anthropokinetics. This is one of the possible perspectives that allows us to analyse such a multifaceted and complex problem as human motor behaviour, which is the only observable manifestation of any mental activity. This is probably the greatest intellectual challenge for all modern science. STA is an original method of thinking about human motor behaviour, which probably reveals its specific aspects and thus may contribute to a better understanding of anthropokinetics. It also enables the construction of an original, novel family tree of science as a whole.